Solar water evaporation adsorption material as well as preparation method and application thereof

By using preoxidized nanocellulose and polyvinyl alcohol to construct a dual network structure in rare earth adsorption materials and loading polydopamine-modified zeolite imidazole ester skeleton materials, the problems of low adsorption capacity and poor stability of existing materials are solved, and high efficiency is achieved , rapid rare earth ion adsorption and solar water evaporation effects.

CN119488889AActive Publication Date: 2025-02-21CENT SOUTH UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411856593.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-02-21
Estimated Expiration
2044-12-17

AI Technical Summary

Technical Problem

Existing rare earth adsorption materials have problems such as low adsorption capacity, poor stability and long adsorption equilibrium time, and it is difficult to take into account both high adsorption capacity and fast adsorption equilibrium.

Method used

Pre-oxidized nanocellulose and polyvinyl alcohol are used to construct a dual network structure, and the zeolite imidazole ester skeleton material loaded with polydopamine modified to form PDA-ZIF-8@CNF/PVA material, with high stability and photothermal conversion functions.

Benefits of technology

It achieves efficient adsorption of rare earth ions, shortens the adsorption kinetic time, improves the stability and adsorption capacity of the material, and can also use solar energy to accelerate water evaporation and adsorption of rare earth ions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119488889A_ABST
    Figure CN119488889A_ABST
Patent Text Reader

Abstract

The invention discloses a solar water evaporation adsorption material as well as a preparation method and application thereof, and belongs to the technical field of wastewater treatment. Stirring and reacting the polydopamine modified zeolite imidazate framework material with the pre-oxidized nano cellulose solution and the polyvinyl alcohol solution to form a viscous liquid, transferring the viscous liquid into a mold, and sequentially performing standing and bubble removal, freeze forming and freeze drying to obtain the polydopamine modified zeolite imidazate framework material. The solar water evaporation adsorption material is formed by a zeolite imidazate framework material which is formed by the pre-oxidized nanocellulose and the polyvinyl alcohol and is modified by loading polydopamine on a dual-network structure. The composite material has the characteristic of high stability, is endowed with a photo-thermal conversion function and rare earth ion adsorption activity at the same time, can promote water evaporation and accelerate mass transfer of rare earth ions in an aqueous solution and combination of adsorption active sites by utilizing solar radiation so as to accelerate adsorption kinetics of the rare earth ions, and can be used for rare earth wastewater treatment. The method is especially suitable for low-concentration rare earth wastewater treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an adsorption material, in particular to a solar water evaporation adsorption material, and also to a preparation method thereof, and to the application of the solar water evaporation adsorption material in purifying rare earth wastewater, belonging to the technical field of wastewater treatment. Background Art

[0002] Rare earth elements, as one of the strategic key metals, are known as "industrial vitamins". Due to their excellent physical and chemical properties, they are widely used in fluorescent materials, permanent magnetic materials and alloy materials. In order to meet the increasing demand for rare earths, the global rare earth production has also increased year by year. However, a large amount of rare earth waste is generated during rare earth mining, processing and end of life, especially wastewater containing low concentrations of rare earths. It is reported that for every ton of rare earth oxide produced from ionic rare earth ores through hydrometallurgy, 1,000 tons of rare earth wastewater will be generated.

[0003] Therefore, it is of great significance to separate and recover rare earth resources from rare earth wastewater. However, traditional methods for recovering rare earths in solutions, such as chemical precipitation, evaporative crystallization, and solvent extraction, have the disadvantages of high energy consumption, low efficiency, and a lot of organic waste liquid. The adsorption method has the advantages of simple operation and large processing capacity, and is a potential means to treat low-concentration rare earth ion wastewater. The existing adsorption materials are mainly mineral-based, carbon-based, polymer-based, and metal-organic framework-based materials. Mineral-based and carbon-based materials are widely available, but have low adsorption capacity. Polymer-based and metal-organic framework-based materials have high adsorption capacity but poor stability. In addition, the adsorption equilibrium time of existing adsorption materials is generally long. Generally speaking, the higher the adsorption capacity, the longer the equilibrium time required. It is difficult to achieve both high adsorption capacity and rapid adsorption equilibrium.

[0004] Solar water evaporator is to place the evaporator at the interface of water and air, and use the heat generated by solar radiation to accelerate the evaporation of water. Its structure is mainly divided into black photothermal conversion material and water transmission matrix material. At present, it is mainly used in seawater desalination, oil (organic pollutant) water separation and medical sterilization. There is no report on the use of solar water evaporator to adsorb and recover rare earth ions. The main reason is that the matrix material is mainly sponge, and there is no active site that can adsorb rare earth ions. Chinese patent (publication number: CN111675275B) reports an application of preparing solar water evaporation materials by wood to adsorb lead ions. The water evaporation material uses the carbonization of wood, one side as a photothermal conversion material, and the other side as a water transmission layer. Although it can adsorb some lead ions, the type of active sites in its channel is single, and adsorption is mainly achieved through pores. In addition, the mechanical properties of wood can be weakened after potassium hydroxide and potassium sulfite remove lignin, and the mechanical stability of the material after carbonization is usually poor, and it is easy to fall off, break and compress during use. Summary of the invention

[0005] In view of the technical shortcomings of rare earth adsorption materials in the prior art, the first purpose of the present invention is to provide a solar water evaporation adsorption material (PDA-ZIF-8@CNF / PVA material), which is composed of a double network structure formed by pre-oxidized nanocellulose and polyvinyl alcohol loaded with a polydopamine-modified zeolite imidazolate framework material, has the characteristics of high stability, and at the same time gives it photothermal conversion function and rare earth ion adsorption activity, can use solar radiation to promote water evaporation, accelerate the mass transfer of rare earth ions in aqueous solution and combine with adsorption active sites, thereby accelerating the adsorption kinetics of rare earth ions, and can be used for rare earth wastewater treatment.

[0006] The second object of the present invention is to provide a method for preparing a solar water evaporation adsorption material, which is simple, has mild conditions, and can be expanded for production.

[0007] The third object of the present invention is to provide a solar water evaporation adsorption material for rare earth wastewater purification, and to construct a solar water evaporator with the solar water evaporation adsorption material to promote the evaporation of rare earth wastewater with the help of solar radiation, accelerate the mass transfer of rare earth ions in the solution and the combination with adsorption sites, speed up the adsorption kinetics, and obtain evaporated condensed water at the same time.

[0008] In order to achieve the above technical objectives, the present invention provides a method for preparing a solar water evaporation adsorption material, which comprises the steps of stirring a polydopamine-modified zeolite imidazolate framework material with a pre-oxidized nanocellulose solution and a polyvinyl alcohol solution to form a viscous liquid, transferring the viscous liquid to a mold, and sequentially performing standing to remove bubbles, freeze molding, and freeze drying to obtain the obtained material.

[0009] The present invention utilizes pre-oxidized nanocellulose and polyvinyl alcohol to construct a dual network structure, and simultaneously loads a polydopamine-modified zeolite imidazolate framework material in the network structure through chemical bonding. The dual network structure constructed by pre-oxidized nanocellulose and polyvinyl alcohol has a rich pore structure, and the network contains a large number of hydrophilic groups such as hydroxyl groups and carboxyl groups with adsorption activity, which is beneficial to the transmission of water and the adsorption of rare earth ions. The polydopamine-modified zeolite imidazolate framework material utilizes its surface-modified polydopamine to bond with oxygen-containing polar groups on the surface of the network structure through groups such as amino groups and phenolic hydroxyl groups to achieve fixation, and its stability is greatly improved, and at the same time, the zeolite imidazolate framework material is highly dispersed in the network structure, which can provide more adsorption active sites, and in addition, polydopamine gives the zeolite imidazolate framework material photothermal conversion performance, and solar radiation can be used to promote water evaporation and improve adsorption kinetics.

[0010] As a preferred solution, the mass concentration of the preoxidized nanocellulose solution is 1-2%. Preoxidized nanocellulose is a nanocellulose preoxidized by Tempo, and its surface is rich in polar hydrophilic oxygen-containing groups such as carboxyl groups. Ordinary cellulose mainly contains alcohol hydroxyl groups and primary alcohol hydroxyl groups, and after Tempo oxidation, the primary alcohol hydroxyl groups at the C6 position can be oxidized to carboxyl groups, and the preoxidized nanofibers containing carboxyl groups play a key role in the formation of gel materials. On the one hand, the carboxyl groups on the preoxidized nanocellulose (CNF) chain are combined with the hydroxyl groups on the polyvinyl alcohol (PVA) chain through hydrogen bonds to construct a double network structure, that is, CNF is one of the aerogel skeletons; on the other hand, the carboxyl groups on the CNF chain are combined with the amino groups of the PDA modified on the outer layer of the zeolite imidazolate skeleton to achieve stable loading of the zeolite imidazolate skeleton, and the polydopamine-modified zeolite imidazolate skeleton is uniformly loaded in the aerogel. Thirdly, the carboxyl group is also an active group for adsorbing rare earth ions. The carboxyl group belongs to a Lewis base and can be combined with rare earth ions (Lewis acid) to achieve adsorption of rare earth ions.

[0011] As a preferred solution, the mass concentration of the polyvinyl alcohol solution is 1-4%. The main chain of polyvinyl alcohol contains a large number of alcohol hydroxyl functional groups, which can form a double network structure aerogel matrix with CNF through hydrogen bonds, and is one of the aerogel skeletons. The double network structure aerogel constructed by the two is more stable than a single polyvinyl alcohol gel or CNF aerogel.

[0012] As a preferred solution, the mass ratio of the pre-oxidized nanocellulose solution to the polyvinyl alcohol solution is 1.5-2:1. When the ratio of CNF is too low, the hydrogen bonding between CNF and PVA is weak, resulting in poor gel stability; when the ratio of CNF is too high, most of the CNF will remain without cross-linking with PVA, resulting in poor gel stability; it is more reasonable that the CNF content is slightly higher than PVA, which ensures that a skeleton can be formed between the two and that some carboxyl groups can capture rare earth ions.

[0013] As a preferred solution, the mass of the polydopamine-modified zeolite imidazolate framework material accounts for 0.5-1% of the mass of the viscous liquid. The polydopamine-modified zeolite imidazolate framework material is a key part of the solar water evaporation material (photothermal conversion material), and also acts as a node (such as Figure 3 As shown in the figure), if too little PDA-ZIF8 is added, the photothermal conversion effect will be poor and it will be difficult to enhance the adsorption process; if too much PDA-ZIF8 is added, it will occupy a large number of carboxyl groups on CNF, thereby reducing the adsorption sites of rare earth ions, which is not conducive to the capture of rare earths.

[0014] As a preferred solution, the mass ratio of polydopamine to zeolite imidazolate framework material in the polydopamine-modified zeolite imidazolate framework material is 2 to 1: 1. If the amount of polydopamine modified on the surface of the zeolite imidazolate framework material is too low, it is difficult to stably load the zeolite imidazolate framework material in the double network structure constructed by pre-oxidized nanocellulose and polyvinyl alcohol, and its photothermal conversion performance is also reduced. If the amount of polydopamine modified on the surface of the zeolite imidazolate framework material is high, the adsorption activity of the zeolite imidazolate framework material will be reduced.

[0015] As a preferred solution, the number average molecular weight of the polyvinyl alcohol in the polyvinyl alcohol solution is 13000 to 23000. Polyvinyl alcohol with a higher molecular weight is more conducive to constructing a gel material.

[0016] As a preferred solution, the reaction conditions are: temperature of 30-50° C. and time of 2-4 h.

[0017] The zeolite imidazolate framework material involved in the present invention is ZIF-8. The zeolite imidazolate framework (ZIF-8) is obtained by an existing preparation method: zinc nitrate hexahydrate and dimethyl imidazole solution are mixed in a certain mass ratio and placed in a water bath for stirring, aging, centrifugation to collect white solid materials, and vacuum drying. Among them, the mass ratio of zinc nitrate hexahydrate to dimethyl imidazole is 1:8~1:10, ensuring that dimethyl imidazole can coordinate with zinc ions to form a metal-organic framework material, the stirring temperature is 30~50°C, the time is 30~60min, and the aging time is 8~12h to ensure its crystal structure growth.

[0018] The preparation method of the polydopamine-modified zeolite imidazolate framework material of the present invention: hydrophilic and stabilized modification of zeolite imidazolate framework material (PDA-ZIF-8): ZIF-8 and an appropriate amount of dopamine are added to a Tris base solution, and the solution is continuously stirred until it turns black, and the black solid material is collected by centrifugation and vacuum dried. The pH value of the Tris base is 8.0-8.8, and stirring for 8-12 hours is conducive to the polymerization of dopamine on its surface under this condition. In addition, the mass ratio of the amount of dopamine added to ZIF-8 is 2-1.

[0019] The present invention also provides a solar water evaporation adsorption material, which is obtained by the preparation method. The solar water evaporation adsorption material is composed of a double network structure formed by pre-oxidized nanocellulose and polyvinyl alcohol loaded with a polydopamine-modified zeolite imidazolate skeleton material. The zeolite imidazolate skeleton material uses its surface-modified polydopamine to chemically bond with hydroxyl and carboxyl groups on the surface of the network structure through phenolic hydroxyl groups, amino groups, etc., greatly improving the loading stability of the zeolite imidazolate skeleton material, and polydopamine gives the adsorption material a photothermal conversion function, and a large number of polar groups and zeolite imidazolate skeleton materials show high rare earth ion adsorption activity, so that solar radiation can be used to promote water evaporation, accelerate the mass transfer of rare earth ions in aqueous solution and combine with adsorption active sites, accelerate the adsorption kinetics of rare earth ions, and can be used for rare earth wastewater treatment. In addition, the double network structure formed by pre-oxidized nanocellulose and polyvinyl alcohol has a rich pore structure, and the pore surface is rich in hydrophilic groups, which is conducive to water transmission.

[0020] The present invention also provides an application of solar water evaporation adsorption material, which is used for rare earth wastewater purification. The solar water evaporation adsorption material is used to construct a solar water evaporator, which promotes the evaporation of rare earth wastewater with the help of solar radiation, accelerates the mass transfer of rare earth ions in the solution and the combination with adsorption sites, speeds up adsorption kinetics, and can obtain evaporated condensed water at the same time.

[0021] As a preferred solution, under sunlight, the solar water evaporation adsorption material obtains evaporated condensed water while adsorbing rare earth metal ions in rare earth wastewater.

[0022] The present invention provides a solar water evaporator, the simplified structural diagram and working principle of which are as follows: Figure 4 As shown. The raw liquid tank (1) is filled with a rare earth ion solution, and the rare earth ion solution passes through the evaporation condensation tank (2) and the recovery tank (3) in sequence along the water transmission channel formed by the cotton gauze (2) through capillary action. In the evaporation condensation tank, the solar evaporation adsorption material (5) placed on the cotton gauze can heat the water adsorbed by the evaporation adsorption material under sunlight, and adsorb the rare earth ions in the solution, and the evaporated water is recovered by condensation and enters the evaporation condensation tank.

[0023] The rare earth wastewater of the present invention may be low-concentration rare earth wastewater, for example, rare earth wastewater with a concentration lower than 200 mg / L.

[0024] Compared with the prior art, the technical solution of the present invention has the following beneficial effects: 1) The PDA-ZIF-8@CNF / PVA material designed by the present invention is used as a solar water evaporator, which has the functions of rare earth ion adsorption and water purification.

[0025] 2) The double network structure gel constructed by hydrogen bonding between CNF and PVA in the PDA-ZIF-8@CNF / PVA material of the present invention has a need to be improved in terms of stability, just like other gel materials. The polyphenol groups and amino groups on the surface of PDA-ZIF-8 can be used as nodes to enhance the bonding with CNF and PVA, thereby increasing the stability of the material and avoiding the use of traditional toxic cross-linking agents, such as the attached Figure 3 As shown, PDA-ZIF-8 is highly dispersed and stably loaded.

[0026] 3) The PDA-ZIF-8@CNF / PVA material of the present invention achieves stable loading of the zeolite imidazolate framework material, avoiding the drawback that the fine-particle metal-organic framework is difficult to recover in solution, while utilizing its excellent photothermal conversion properties to accelerate its adsorption kinetics (rare earth ion adsorption is an endothermic process, and an increase in temperature is conducive to adsorption).

[0027] 4) The PDA-ZIF-8@CNF / PVA material of the present invention has abundant hydrophilic pores that allow aqueous solutions to freely enter and exit. At the same time, nanocellulose and polydopamine have abundant carboxyl, hydroxyl and amino functional groups that are Lewis bases that can coordinate with rare earth cations (Lewis acids) to achieve selective adsorption.

[0028] 5) The preparation method of the PDA-ZIF-8@CNF / PVA material of the present invention is simple, the conditions are mild, and it is conducive to expanding production.

[0029] In summary, the PDA-ZIF-8@CNF / PVA material of the present invention has the following obvious advantages: the phenolic hydroxyl and amino functional groups on the surface of the zeolite imidazolate skeleton (ZIF-8) modified by polydopamine (PDA) can react with nanocellulose (carboxyl) and polyvinyl alcohol (hydroxyl) to become the nodes of the double network structure aerogel, thereby enhancing the stability of the aerogel; and PDA-ZIF-8 has a photothermal conversion function, which provides energy for the adsorption of rare earth ions (endothermic process) and accelerates the adsorption kinetics. At the same time, the rich oxygen-containing and nitrogen-containing (Lewis base) in the aerogel provides a large number of binding sites for the adsorption of rare earth ions (Lewis acid), thereby ensuring a high adsorption capacity; the loading of the zeolite imidazolate skeleton material is achieved, thereby avoiding the problem that metal-organic framework materials (nano / micrometer-level materials) are difficult to recycle. Under sunlight, the solar water evaporation material using the material can achieve more than 90% of rare earth ion removal, and at the same time obtain evaporated condensed water. It can be seen that the solar water evaporation material based on the zeolite imidazolate skeleton of the present invention has the dual functions of key metal recovery and water resource purification. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a physical picture of PDA-ZIF-8@CNF / PVA material.

[0031] Figure 2 This is a physical picture of CNF / PVA material (the ratio of CNF to PVA is 2:1).

[0032] Figure 3 Schematic diagram of the network structure of PDA-ZIF-8@CNF / PVA material.

[0033] Figure 4 Schematic diagram of the working principle of PDA-ZIF-8@CNF / PVA material as a solar water evaporation device.

[0034] Figure 5 This is a physical picture of CNF / PVA material (the ratio of CNF to PVA is 1:5). DETAILED DESCRIPTION

[0035] In order to make the objectives, technical solutions and beneficial effects of the present invention more clear, specific implementation modes of the present invention are described in detail below with reference to the accompanying drawings.

[0036] The following examples are merely illustrative and are not intended to limit the scope of protection of the claims of the present invention. Unless otherwise specified, the chemicals used in the examples are all commercially available products.

[0037] Example 1

[0038] 1) Preparation of ZIF-8: 4 mL of 25 g / L zinc nitrate hexahydrate solution was added to 20 mL of 40 g / L dimethylimidazole solution, stirred in a 35°C water bath for 40 min, and aged for 10 h. ZIF-8 material was separated by centrifugation and vacuum dried.

[0039] 2) Preparation of PDA-ZIF-8: 500 mg of ZIF-8 was placed in a Tris base solution (500 mL) with a pH of 8.5, and 800 mg of dopamine was added. The mixture was stirred for 10 h until the solution turned completely black. The PDA-ZIF-8 material was obtained by centrifugation and vacuum dried.

[0040] 3) PDA-ZIF-8@CNF / PVA: Take 20g of nanocellulose solution (mass fraction 2%) pretreated by Tempo oxidation and mix with 10g of polyvinyl alcohol (average molecular weight of about 20,000) solution (mass fraction 2%) and add 300mg PDA-ZIF-8. Stir in a 40℃ water bath for 3h to obtain a black viscous liquid, pour it into a mold and let it stand for 12h to remove bubbles, then place it in a -20℃ refrigerator and freeze it for 8h, and finally freeze-dry it to obtain PDA-ZIF-8@CNF / PVA aerogel material. Figure 1As shown, the aerogel surface has abundant pores, a black appearance, and can be placed on the surface of a leaf, proving that its light density can be used for evaporation at the water-air interface.

[0041] 4) Rare earth adsorption experiment: Figure 4 Assemble the solar water evaporator, where 1 is the original liquid tank containing rare earth ion solution, 2 is the evaporation condensation tank, 3 is the recovery tank, 4 is the cotton gauze that acts as a water transmission channel (water can be transported from tank 1 to tank 3 through capillary phenomenon) and can also support the solar evaporation material, 5 is the PDA-ZIF-8@CNF / PVA aerogel placed on the surface of the cotton gauze, which can add water and evaporate under sunlight and adsorb rare earth ions in the solution, and 6 and 7 are both electronic balances. During the experiment, 100 mg / L rare earth Gd ion solution was poured into the original liquid tank 1, and the other parts were built and placed outdoors under sunlight. The removal rate of rare earth ions was calculated by measuring the difference in rare earth mass between the recovery tank No. 3 and the original liquid tank No. 1. After measurement, the calculated rare earth removal rate was 92.5% after 30 minutes, which has a good rare earth removal effect, and the refluxed evaporated water was observed in the condensation tank, indicating that the material has good photothermal efficiency.

[0042] Comparative Example 1 The CNF / PVA aerogel material was prepared in the same manner as in Example 1, except that PDA-ZIF-8 was not added in Comparative Example 1, that is, 20 g of nanocellulose solution (mass fraction 2%) pretreated by Tempo oxidation was mixed with 10 g of polyvinyl alcohol (average molecular weight of about 20,000) solution (mass fraction 2%) and placed in a 40°C water bath for stirring for 3 h to obtain a viscous liquid, which was poured into a mold and allowed to stand for 12 h to discharge bubbles, and then placed in a -20°C refrigerator for 8 h, and finally freeze-dried to obtain the CNF / PVA aerogel material. The materials are as shown in the attached Figure 2 As shown, the material surface is a white porous material with a light density and can be placed above the blades.

[0043] Rare earth adsorption experiment: Placed outdoors under sunlight as in Example 1. The removal rate of rare earth ions was calculated by measuring the difference in the rare earth mass in the No. 3 recovery bin and the No. 1 stock bin. After measurement, the calculated rare earth removal rate was 7.2% after 30 minutes, and the rare earth removal effect was poor. A small amount of water mist was observed on the surface of the No. 2 condensation bin, indicating that the photothermal efficiency was low.

[0044] Experimental results show that PDA-ZIF-8 plays a key role in the water evaporation process. Although the carboxyl functional groups in cellulose can serve as adsorption sites for rare earth ions, it is difficult to combine with other rare earth ions when the aerogel absorbs the solution saturated, resulting in low removal rate and poor evaporation effect.

[0045] Comparative Example 2 The PDA-ZIF-8@CNF / PVA aerogel material was prepared in the same manner as in Example 1, except that the evaporator in the comparative example 2 of the rare earth adsorption experiment was placed in a closed lightless environment indoors. The removal rate of rare earth ions was calculated by measuring the difference in the rare earth mass in the No. 3 recovery bin and the No. 1 original liquid bin. After measurement, the rare earth removal rate was calculated to be 11.4% after 30 minutes, the rare earth removal effect was poor, and no water mist was observed on the surface of the No. 2 condensation bin; after 2 hours, the rare earth removal rate was calculated to be about 13.8%, no water mist was observed on the surface of the No. 2 condensation bin, and the liquid level in the recovery bin remained basically unchanged.

[0046] The experimental results show that the adsorption kinetics of PDA-ZIF-8@CNF / PVA can be accelerated under light conditions. In the absence of light, when the solution in PDA-ZIF-8@CNF / PVA is saturated, the mass transfer rate decreases, making it difficult to adsorb other ions, resulting in poor removal effect.

[0047] Example 2 The same preparation method of ZIF-8 and PDA-ZIF-8 was adopted as in Example 1, except for the amount of CNF and PVA added in step 3).

[0048] 3) PDA-ZIF-8@CNF / PVA: 20 g of nanocellulose solution (mass fraction 2%) pretreated by Tempo oxidation was mixed with 12 g of polyvinyl alcohol (average molecular weight of about 20,000) solution (mass fraction 2%) and 300 mg of PDA-ZIF-8 was added.

[0049] The same test was conducted, that is, under outdoor lighting conditions, the removal rate of rare earth ions was calculated by measuring the difference in the rare earth mass in the No. 3 recovery bin and the No. 1 stock bin. After measurement, the calculated rare earth removal rate was 90.2% after 30 minutes, which has a good rare earth removal effect, and the reflux of evaporated water was observed in the condensation bin, indicating that the material has good photothermal efficiency.

[0050] Comparative Example 3 Similar to comparative example 1, this comparative example mainly investigates the effect of the ratio of nanocellulose solution pretreated by Tempo oxidation to polyvinyl alcohol solution on the stability of aerogel. In the experiment, 2g of nanocellulose solution pretreated by Tempo oxidation (mass fraction of 2%) was mixed with 10g of polyvinyl alcohol (average molecular weight of about 20,000) solution (mass fraction of 2%) and placed in a 40°C water bath for stirring for 3h to obtain a viscous liquid. The liquid was poured into a mold and allowed to stand for 12h to discharge bubbles, then placed in a -20°C refrigerator for 8h, and finally freeze-dried to obtain CNF / PVA aerogel material. The materials are as shown in the attached Figure 5As shown, the surface of the material is a white porous material, which breaks after freeze-drying and has an incomplete surface. This is because less nanocellulose is added after Tempo oxidation pretreatment, resulting in a limited number of carboxyl groups in its structure and hydroxyl groups in the polyvinyl alcohol structure bonded through hydrogen bonds, resulting in poor stability and brittle texture.

Claims

1. A method for preparing a solar water evaporation adsorption material, characterized in that: The polydopamine-modified zeolite imidazolate skeleton material is stirred and reacted with a pre-oxidized nanocellulose solution and a polyvinyl alcohol solution to form a viscous liquid, and the viscous liquid is transferred to a mold and sequentially subjected to standing and degassing, freeze molding and freeze drying to obtain the product.

2. The method for preparing a solar water evaporation adsorption material according to claim 1, characterized in that: The mass concentration of the pre-oxidized nanocellulose solution is 1-2%; The mass concentration of the polyvinyl alcohol solution is 1-4%; The mass ratio of the pre-oxidized nanocellulose solution to the polyvinyl alcohol solution is 1.5-2:

1.

3. The method for preparing a solar water evaporation adsorption material according to claim 1 or 2, characterized in that: The mass of the polydopamine-modified zeolite imidazolate framework material accounts for 0.5-1% of the mass of the viscous liquid.

4. The method for preparing a solar water evaporation adsorption material according to claim 1, characterized in that: The mass ratio of polydopamine to zeolite imidazolate framework material in the polydopamine-modified zeolite imidazolate framework material is 2-1:

1.

5. The method for preparing a solar water evaporation adsorption material according to claim 1 or 2, characterized in that: The number average molecular weight of the polyvinyl alcohol in the polyvinyl alcohol solution is 13000-23000.

6. A method for preparing a solar water evaporation adsorption material according to claim 1, 2 or 4, characterized in that: The reaction conditions are: temperature of 30-50°C and time of 2-4h.

7. A solar water evaporation adsorption material, characterized in that: Obtained by the preparation method according to any one of claims 1 to 6.

8. The use of a solar water evaporation adsorption material according to claim 7, characterized in that: Used for purification of rare earth wastewater.

9. The use of a solar water evaporation adsorption material according to claim 8, characterized in that: Under the irradiation of sunlight, the solar water evaporation adsorption material obtains evaporated condensed water while adsorbing rare earth metal ions in rare earth wastewater.

Citation Information

Patent Citations

  • Preparation method of solar-evaporated water and highly efficient metal ion adsorption materials

    CN111675275B

  • Wood-based composite material for photo-thermal purification of sewage as well as preparation method and application of wood-based composite material

    CN113815072A

  • Cellulose nanofiber aerogel photo-thermal interface water evaporation material and preparation method thereof

    CN114405421A

  • Synthesis of BIO-based catecholic acid- and derivatives-functionalized adsorbents for recovery of metals and metalloids from acidic solutions

    WO2024233637A2